Manejo agronómico de la sigatoka negra (Mycosphaerella fijiensis M.) en la finca Leche y Miel productora de Banano Orgánico (Musa AAA) - Goyes Ugaldi, Kevin Geovanny (2019)
The present research work was carried out at the Banana Leche y Miel with the objective of obtaining information and, above all, knowledge about the agronomic management of black sigatoka in organic banana cultivation and disseminating which phytosanitary controls should be carried out. Among the general methods that were applied to the study, the deductive and inductive methods were used for this investigation, because the hypothesis was raised and verified throughout the development of the research in order to reach the conclusions and recommendations of the work. In the interview with the banana owner, it was learned that the phytosanitary effects for the management of sigatoka in an organic banana farm are different and that he, along with his technicians and workers take all the necessary measures to control the incidence of this disease, performing all phytosanitary practices from the identification of the first stages of the disease to the control with the fungicide because the banana crop requires. It is of vital importance that all personnel working in the milk and honey farm have the appropriate knowledge for the management of each of the activities that are carried out on this farm and especially the importance of each of them that contribute in the management and control of the sigatoka